Developing Creative Competencies in Students Through Flipped Classroom in Fine Arts Education - Muzafarova Sanobar Murodullayevna (ILMIY YANGILIKLAR VA INTELLEKTUAL TADQIQOTLAR, 2025)
Abstract: This article explores the role of the flipped classroom model in developing students’ creative competencies in fine arts education. It emphasizes how pre-class theoretical learning, combined with in-class practical activities and collaborative projects, enhances students’ compositional thinking, aesthetic judgment, and independent problem-solving abilities. The study also highlights the importance of teacher guidance, constructive feedback, and digital tools in creating a supportive environment that nurtures students’ creativity. The article argues that integrating flipped classroom strategies fosters both individual and collective artistic growth, preparing students for academic and professional success.